Antiplasmodial and Cytotoxic Activities of Extracts of Selected Medicinal Plants Used to Treat Malaria in Embu County, Kenya - Bibianne Waiganjo; Gervason Moriasi; Jared Onyancha; Nelson Elias; Francis Muregi (Journal of Parasitology Research)
Malaria is a deadly disease caused by a protozoan parasite whose mode of transmission is through a female Anopheles mosquito. It affects persons of all ages; however, pregnant mothers, young children, and the elderly suffer the most due to their dwindled immune state. The currently prescribed antimalarial drugs have been associated with adverse side effects ranging from intolerance to toxicity. Furthermore, the costs associated with conventional approach of managing malaria are arguably high especially for persons living in low-income countries, hence the need for alternative and complementary approaches. Medicinal plants offer a viable alternative because of their few associated side effects, are arguably cheaper, and are easily accessible. Based on the fact that studies involving antimalarial medicinal plants as potential sources of efficacious and cost-effective pharmacotherapies are far between, this research was designed to investigate antiplasmodial and cytotoxic activities of organic and aqueous extracts of selected plants used by Embu traditional medicine practitioners to treat malaria. The studied plants included Erythrina abyssinica (stem bark), Schkuhria pinnata (whole plant), Sterculia africana (stem bark), Terminalia brownii (leaves), Zanthoxylum chalybeum (leaves), Leonotis mollissima (leaves), Carissa edulis (leaves), Tithonia diversifolia (leaves and flowers), and Senna didymobotrya (leaves and pods). In vitro antiplasmodial activity studies of organic and water extracts were carried out against chloroquine-sensitive (D6) and chloroquine-resistance (W2) strains of Plasmodium falciparum. In vivo antiplasmodial studies were done by Peter’s four-day suppression test to test for their in vivo antimalarial activity against P. berghei. Finally, cytotoxic effects and safety of the studied plant extracts were evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) rapid calorimetric assay technique. The water and methanolic extracts of T. brownii and S. africana and dichloromethane extracts of E. abyssinica, S. pinnata, and T. diversifolia leaves revealed high in vitro antiplasmodial activities (IC50≤10 μg/ml). Further, moderate in vivo antimalarial activities were observed for water and methanolic extracts of L. mollissima and S. africana and for dichloromethane extracts of E. abyssinica and T. diversifolia leaves. In this study, aqueous extracts of T. brownii and S. africana demonstrated high antiplasmodial activity and high selectivity indices values (SI≥10) and were found to be safe. It was concluded that T. brownii and S. africana aqueous extracts were potent antiplasmodial agents. Further focused studies geared towards isolation of active constituents and determination of in vivo toxicities to ascertain their safety are warranted.